The regional relationship between CSF VEGF and white matter microstructural integrity in older adults: A voxelwise DTI study. (20th December 2022) - Tubi, Meral A; Hare, Evan; Nir, Talia M; Sagare, Abhay P; Wang, Xinhui; Schneider, Lon S.; Joe, Elizabeth B; Toga, Arthur W.; Harrington, Michael G; Zlokovic, Berislav V; Chui, Helena C; Braskie, Meredith N
Abstract: Background: Both white matter (WM) micro‐ and macro‐ structural abnormalities occur in Alzheimer's disease (AD) with micro‐structural abnormalities likely preceding macrostructural changes in the AD cascade. Diffusion tensor imaging (DTI) fractional anisotropy (FA) ‐ which is sensitive to factors such as myelination, fiber coherence, and fiber density‐ within an MRI voxel may be used to detect AD‐specific deficits. However, mechanisms driving loss of WM microstructural integrity in AD are poorly understood. Vascular endothelial growth factor (VEGF) is a multi‐function vascular protein linked to early AD brain and cognition biomarkers. VEGF provides neurotrophic support via glia and is also secreted by glial cells essential for maintaining myelin. However, in humans, the relationship between VEGF and WM microstructural integrity has yet to be mapped. We evaluated whether cerebrospinal fluid (CSF) VEGF levels were associated with voxelwise WM FA in older adults without dementia. Method: We evaluated 72 older adults without dementia from the USC Alzheimer's Disease Research Center (ADRC) (mean age 65.7; 47‐82 years old) with a clinical dementia rating (CDR) score of 0 (n=56) or 0.5 (n=16) who had both CSF VEGF‐A levels and a 3 T diffusion MRI scan (64‐direction (b=1000 s/mm2) DWI volumes). MRI scans were pre‐processed to reduce artifacts related to motion, distortion, eddy currents, bias field, and susceptibility artifacts. Tract‐based spatial statistics, using FSL software, was implemented to derive skeletonized FA maps along WM tracts. The association between VEGF and voxelwise FA WM integrity was evaluated using FSL's general linear model tool. We covaried for age, sex, and CDR. FA significance cluster maps were corrected for voxelwise multiple comparisons. Result: Higher CSF VEGF levels were associated with lower DTI FA, indicative of poorer WM microstructural integrity, in the left and right superior longitudinal fasciculus, left anterior thalamic radiation, and left inferior frontal occipital fasciculus (p<0.05) (Figure 1 ). Conclusion: These results demonstrate for the first time in humans that VEGF levels are related to WM microstructure in older adults without dementia, primarily in long range association fibers connecting temporal, parietal, and frontal lobes. These pathways are essential for memory, language, attention and emotional control.